Implementasi Program Bengkel Inggris pada Anak Usia Sekolah Dasar di Desa Klambir Lima Kebun - Fitri Ayu; Devi Anggraini; Nizamuddin (Arsil Media, 2024)
English was realized as one of the international languages, especially in 5.0. Mastering English was not a new thing. It has been a common competency nowadays. That is why all the young generation must know about English. There were children in Indonesia who still do not know and notice the significance of English. It was seen through a survey in Desa Klambir Lima Kebun that the children living there acted as the objects of this community service. Furthermore, this was focused on improving their English achievement through a program named Bengkel Inggris. In this program, the students were distinguished based on their background in English whether basic or middle. Then, they followed the class based on their background. After that, there is a sharing session special for the children. The meeting was done once a week for two months. As a result, there were many improvements gathered from this program not only a better achievement in English score but also a better motivation for learning English. It concluded that improving English achievement through the Bengkel Inggris Program for Children in Klambir Lima Kebun Village succeeded to be done.